2014
DOI: 10.1155/2014/493732
|View full text |Cite
|
Sign up to set email alerts
|

Healing Efficacy of an EGF Impregnated Triple Gel Based Wound Dressing: In Vitro and In Vivo Studies

Abstract: To accomplish an ideal wound healing process which promotes healthy tissue growth with less scaring, a novel gel based topical drug delivery system composed of 3 different polymers chitosan, dextran sulfate, and polyvinylpyrrolidone K30 (CDP) was prepared. The physicochemical properties of the prepared gels were investigated in vitro. Gels showed a maximum swelling ratio of 50 ± 1.95 times of dried gel in PBS at pH 7.4. The swelling ratios increase in acidic and alkaline pH to 55.3 ± 1.75 and 65.5 ± 2.42, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
0
13
0
6
Order By: Relevance
“…This suggested that the developed film has longer residence time on the wound site especially in suppurating wound accredited to its deformation resistant [42]. As reported by Khanbanha et al [49], the higher the viscosity value of a hydrocolloid film dressing, the better the dressing at maintaining the integrity of a drug delivery device.…”
Section: Discussionmentioning
confidence: 67%
“…This suggested that the developed film has longer residence time on the wound site especially in suppurating wound accredited to its deformation resistant [42]. As reported by Khanbanha et al [49], the higher the viscosity value of a hydrocolloid film dressing, the better the dressing at maintaining the integrity of a drug delivery device.…”
Section: Discussionmentioning
confidence: 67%
“…Since LY has a positive charge, the surface potential of the LY shell exceeds zero, and thus it can attract molecules with negative charges. Therefore, the LY shell with positive charges can be adsorbed onto EGF that has a negative charge at pH values above 4.6 (which is the isoelectric pH of EGF) by electrical adsorption 29 , 30 . LYMBs were prepared according to the procedure used in our previous study 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have described new drugs that can promote wound healing without infection and decrease scar formation. [5][6][7][8] Epidermal growth factor (EGF) is secreted by platelets, monocytes and fibroblasts, and stimulates epidermal cells, fibroblasts, smooth muscle cells and endothelial cells to promote wound granulation and angiogenesis. Recombinant human epidermal growth factor (rhEGF) has been reported to improve wound healing in diabetic foot ulcer and radiation-related oral mucositis without major side effects.…”
Section: Introductionmentioning
confidence: 99%